Storage, enhancement and preservation of doctoral dissertations in the experience “Magazzini digitali”: a contribution to research and access - Storti, Chiara (JLIS.it, 2019)
This contribution traces the history of the legal deposit of Doctoral thesis in Italy from the National Central Library of Florence’s point of view, in order to constitute a guide for research and access. Since 2006 the National Library of Florence manages the national digital preservation and long-term access service called “Magazzini Digitali” (“Digital Stocks”).